Ecological Restoration of A Logged-over Area in the South Bolaang Mongondow Rainforest - Langi, M A; Saroyo, Saroyo (EUGENIA, 2018)
This research has been conducted over the past 12 years and was aimed to gain understanding on the complex interactions involved in the maintaining and restoring biodiversity that might influence the flow of ecosystem services. The method used in this study is annual measurement and observation conducted through surveys into similar sites conducted in every November to December since 2004.Â  Stand structures consist of indicators of tree density, tree structure, crown coverage, and species composition.Â  Function and sustainability are describes through biodiversity (Shannon index), natural colonization (abundance), wildlife density and status (species richness), nutrient retention (litter fall and decomposition), soil and water quality (erosion and sedimentation, soil physics, water debit and clarity).Â  This study is still going on addressing an important question, that is â€œHow long does it take for degraded forest land to achieve certain biodiversity or functional outcomes?â€ In relation to that, some indicators have begun to show certain patterns and tendencies.